EVALUASI ARUS KAS TERHADAP AKTIVITAS PERDAGANGAN PERUSAHAAN EFEK - Siska P. Yudowati (Profita : Komunikasi Ilmiah Akuntansi dan Perpajakan, 2016)
Investors will open the Client Fund Account at securities firms that have a good performance. The company's performance can be judged a good effect on the company's operational effects described through financial reports, especially reports good operating cash flow. Cash flows from operating activities are derived primarily from the principal revenue-producing activities of the entity. If the securities company has a good performance it will have an impact on the number of investors who entrust the company's services so that the volume of these securities buy and sell securities increased. Samples were securities companies listed on the Indonesia Stock Exchange that have degan using purposive sampling method. Criteria sample in this study is a securities company entered into 15 highest trading volume for 5 years from 2010 s.d 2014 as many as seven companies. The results of the study explained that the company's performance is measured by the effect of the efficiency and adequacy of simultaneously operating cash flow does not affect the company's stock trading volume effect. Both the efficiency and adequacy of the operating cash flow of each partial no effect on the company's stock trading volume effect. They can only explain the trading volume amounted to 3.4548%.